Microbial anaerobic Fe(II) oxidation – Ecology, mechanisms and environmental implications. (10th October 2018) - Bryce, Casey; Blackwell, Nia; Schmidt, Caroline; Otte, Julia; Huang, Yu‐Ming; Kleindienst, Sara; Tomaszewski, Elizabeth; Schad, Manuel; Warter, Viola; Peng, Chao; Byrne, James M.; Kappler, Andreas
Summary: Iron is the most abundant redox‐active metal in the Earth's crust. The one electron transfer between the two most common redox states, Fe(II) and Fe(III), plays a role in a huge range of environmental processes from mineral formation and dissolution to contaminant remediation and global biogeochemical cycling. It has been appreciated for more than a century that microorganisms can harness the energy of this Fe redox transformation for their metabolic benefit. However, this is most widely understood for anaerobic Fe(III)‐reducing or aerobic and microaerophilic Fe(II)‐oxidizing bacteria. Only in the past few decades have we come to appreciate that bacteria also play a role in the anaerobic oxidation of ferrous iron, Fe(II), and thus can act to form Fe(III) minerals in anoxic settings. Since this discovery, our understanding of the ecology of these organisms, their mechanisms of Fe(II) oxidation and their role in environmental processes has been increasing rapidly. In this article, we bring these new discoveries together to review the current knowledge on these environmentally important bacteria, and reveal knowledge gaps for future research.